2006
DOI: 10.3171/jns.2006.104.5.720
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of cellular edema in traumatic brain swelling in patients with severe head injuries

Abstract: The brain swelling observed in patients with TBI appears to be predominantly cellular, as signaled by low ADC values in brain tissue with high levels of water content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(103 citation statements)
references
References 33 publications
2
100
0
1
Order By: Relevance
“…This could be due to brain water accumulation being more reduced after diffuse TBI than after occlusion of a terminal brain artery in rats: 0.5% to 1% in this TBI model (Cernak et al, 2004) versus 2% to 4% in models of ischemia (Barbier et al, 2005;Lin et al, 2000). Similarly, moderate brain water accumulation was reported in diffusely head-injured patients presenting brain swelling and concomitant elevated intracranial pressure (Marmarou et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…This could be due to brain water accumulation being more reduced after diffuse TBI than after occlusion of a terminal brain artery in rats: 0.5% to 1% in this TBI model (Cernak et al, 2004) versus 2% to 4% in models of ischemia (Barbier et al, 2005;Lin et al, 2000). Similarly, moderate brain water accumulation was reported in diffusely head-injured patients presenting brain swelling and concomitant elevated intracranial pressure (Marmarou et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Diffuse damage or a stroke may also result in diffuse swelling of the brain, but in all cases, swollen regions are associated with dead, dying or damaged cells (Kawamata et al 2007). Imaging studies have identified cytotoxic swelling as the most probable cause of this oedema (Vorisek et al 2002;Maeda et al 2003;van Pul et al 2005;Marmarou et al 2006b;Kuroiwa et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of this type of SIS will depend on which phase of metabolic recovery the brain is in when the second concussion occurs. The severe brain swelling observed in SIS (11,14,21,44,55,64) is probably attributable to the fact that the second insult took place when the cells were still intensely engaged in restoration of their energetic integrity and were unable to withstand further mitochondrial damage, thus experiencing uncontrolled swelling and massive NAA loss (47).…”
Section: Significance Of Posttraumatic Naa Reduction and Recoverymentioning
confidence: 99%